Reaction of bisphenol A with synthetic and commercial MnOx(s): spectroscopic and kinetic study. Issue 7 (14th June 2018) - Shaikh, Nabil; Zhang, Huichun; Rasamani, Kowsalya; Artyushkova, Kateryna; Ali, Abdul-Mehdi S.; Cerrato, José M.
Abstract : The reaction of bisphenol A (BPA) using laboratory synthesized (Syn-MnO x ) and commercially available (Com-MnO x ) MnO x (s) media was investigated using spectroscopic and aqueous chemistry methods. Abstract : The reaction of bisphenol A (BPA) using laboratory synthesized (Syn-MnO x ) and commercially available (Com-MnO x ) MnO x (s) media was investigated using spectroscopic and aqueous chemistry methods. The surface area of Syn-MnO x (128 m 2 g −1 ) and Com-MnO x (13.6 m 2 g −1 ) differed by an order of magnitude. The impurities were less than 1% by weight for Syn-MnO x while Com-MnO x contained 29% impurity by weight, mainly Al, Si and Fe. The removal of 99.7% BPA was observed applying Syn-MnO x, while 71.2% BPA removal was observed applying Com-MnO x after 44 hours of reaction of 10 mM MnO x (s) media with 1 mM BPA at pH 5.5. The reduction of Mn was detected in the surface of both BPA reacted media, but a higher content of reduced Mn was observed in Syn-MnO x (52% in Syn-MnO x compared to 29% in Com-MnO x ). The release of soluble Mn was an order of magnitude higher in batch experiments reacting BPA with Syn-MnO x compared with Com-MnO x . The C 1s and O 1s XPS high resolution spectral analyses identified the presence of functional groups that likely correspond to BPA oxidation products, such as dimers and quinones associated with MnO x (s) surfaces on both reacted media. The reaction of BPA with Syn-MnO x fit the electron transfer-limited model ( R 2 = 0.96), while the reaction of BPA with Com-MnO x had a better fit for surface complex formation-limited model ( R 2 = 0.95). These results suggest that BPA removal and the reactivity of MnO x (s) are affected by the differences in surface area and impurities present in these media. Thus, this study has relevant implications for the reaction of MnO x (s) with emerging organic contaminants in natural biogeochemical processes and water treatment applications.